The migration of fin whales into the southern Chukchi Sea as monitored with passive acoustics. (26th January 2016) - Tsujii, Koki; Otsuki, Mayuko; Akamatsu, Tomonari; Matsuo, Ikuo; Amakasu, Kazuo; Kitamura, Minoru; Kikuchi, Takashi; Miyashita, Kazushi; Mitani, Yoko
Abstract: Fin whales ( Balaenoptera physalus ) undergo seasonal migration in the Arctic Sea. Because their migration and distribution is likely affected by changes in global climate, we aimed to examine the migration timing of fin whales, and the relationship with prey availability within the oceanographic environment of the Arctic Sea, using passive and active acoustic monitoring methods. Automatic Underwater Sound Monitoring Systems were deployed in the southern Chukchi Sea from July 2012 to 2014 to determine the acoustic presence of fin whales. Furthermore, water temperature and salinity were recorded by a fixed data logger. An Acoustic Zooplankton Fish Profiler was additionally deployed to estimate prey abundance through backscattering strength. Sea ice concentrations were obtained by remote sensing data. Fin whale calls were automatically detected using a custom-made software, and the per cent of half-hours containing calls were counted. Fin whale calls were detected from 4 August to 20 October 2012 (78 d) and 25 July to 1 November 2013 (100 d). The extended period of acoustic presence of fin whales during 2013 when compared with 2012 is likely related to a longer ice-free period during 2013. Furthermore, generalized linear model analyses showed that half-hour periods containing calls increased with a rise in water temperature and zooplankton abundance during the initial call presence period, while they decreased with a decrease in water temperature and salinity during the end of the call presence period. Our results suggest that the rise in water temperature and zooplankton abundance affect the timing of migration of fin whales in a way that is consistent with the expansion of their suitable habitats and the extension of their presence in the Arctic Sea.